Using the Canadian Speech Research Environment (CSRE) to teach speech perception to undergraduates - Cheesman, M.F.; Jamieson, D.G. (Canadian Acoustics, 1993)
This paper describes four computer-based learning sessions that were designed for and used in the speech acoustics and perception sections of a course in Speech Science offered by the Department of Communicative Disorders at the University of Western Ontario. Students enrolled in the course have undergraduate degrees in diverse disciplines, including the physical, social, and biological sciences, arts and humanities. Consequently, students vary greatly in their previous experiences with audio and computer hardware, computer software packages, and in their knowledge of speech perception and physical and speech acoustics